Helen Jacquet-Gordon, 1918–2013 - Johnson, W. Raymond.
It is with great sadness that we announce the passing of Helen Jacquet-Gordon, 95, at her home in Carouge, Switzerland, on April 26th, 2013, with her beloved husband Jean by her side. The loss to Egyptology is profound; Helen was a true Renaissance woman who specialized in ancient Egyptian ceramics but was proficient in the language, epigraphy, art, history, and archaeology of ancient Egypt and the Sudan, and was herself an accomplished artist and musician.